APPLICATION OF LOCAL AND MINERAL FERTILIZERS DEPENDING ON THE LEVEL OF SOIL SUPPLY (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This study examined the impact of soil reserves and soil minerals on improving utilization efficiency. This work shows the importance and benefits of local and mineral fertilizers for improving soil quality, plant growth and development. In addition, the study focuses on the differentiated use of local and mineral fertilizers depending on the level of their availability.